The Translation Process: Methods and Problems of its Investigation - Lörscher, Wolfgang (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractAfter the introductory remarks about the analysis of mental translation processes (section 1) and an outline of the investigation reported on in this paper (section 2) the methodology used is presented (section 3). It consists of the methods for data elicitation as well as for data analysis and evaluation. Section 4 describes a strategic analysis of translation processes carried out on three levels: the level of the elements of translation strategies (4.1), of the strategies themselves (4.2) and of the translation versions (5). The paper terminates with a brief comparison of professional and non-professional translation processes (section 6).